2019
DOI: 10.1021/acs.jpcb.9b07278
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Energy Landscapes Reveals Dynamic Features That Contribute to Binding of Inhibitors to CFTR-Associated Ligand

Abstract: The CFTR-associated ligand PDZ domain (CALP) binds to the cystic fibrosis transmembrane conductance regulator (CFTR) and mediates lysosomal degradation of mature CFTR. Inhibition of this interaction has been explored as a therapeutic avenue for cystic fibrosis. Previously, we reported the ensemble-based computational design of a novel peptide inhibitor of CALP, which resulted in the most binding-efficient inhibitor to date. This inhibitor, kCAL01, was designed using OSPREY and evinced significant biological ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…Osprey software was used to predict mutations in the B domain to increase binding affinity. , In the first B domain–Fab interface, the best score was predicted for conformation mutations Lys824Arg, Ilu834Leu, Ala837Thr, Lys840Arg, and Leu856Trp with the binding energy of −2603.446 kcal mol –1 . In the second B domain–Fab interface, the lowest-energy predicted conformation with the top-ranked mutations included Phe843Tyr, Thr847Met, Ala848Arg, Thr865Trp, and Gly871Trp with the binding energy of −3006.986 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osprey software was used to predict mutations in the B domain to increase binding affinity. , In the first B domain–Fab interface, the best score was predicted for conformation mutations Lys824Arg, Ilu834Leu, Ala837Thr, Lys840Arg, and Leu856Trp with the binding energy of −2603.446 kcal mol –1 . In the second B domain–Fab interface, the lowest-energy predicted conformation with the top-ranked mutations included Phe843Tyr, Thr847Met, Ala848Arg, Thr865Trp, and Gly871Trp with the binding energy of −3006.986 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that mutation prediction using Ospery not only led to an increase in the binding affinity but also increased the protein stability. , Lys824Arg and Lys840Arg mutations in the first binding site and Phe843Tyr and Thr847Met mutations in the second binding site predicted improvement of the protein stability. Sokalingam et al reported that the lysine to arginine mutagenesis could increase the mutant protein stability in the presence of chemical denaturants such as urea, alkaline pH, and ionic detergents .…”
Section: Resultsmentioning
confidence: 99%
“…In general, we and others are attempting to use available sequence and structural information to predict binding affinities with the goal of identifying cellular interaction networks (e.g., refs. Gerek et al, 2009;Gerek and Ozkan, 2010;Gfeller et al, 2011;Holt et al, 2019;Landgraf et al, 2004;te Velthuis et al, 2011;Tian et al, 2011;Valgardson et al, 2019). Understanding structural flexibility is important to these studies (Roberts et al, 2012;Thomas et al, 2009).…”
Section: There Is No "Ile" In "Thr-glu-ala-met" or How All Of The Rementioning
confidence: 99%
“… 174 Structure and energy landscape analysis of the crystal structure of 41 :CALP (PDB ID: 6OV7) showed that the tighter binding efficiency of 41 could stem from entropic effect at P0 and favorable substitutions at P-1 and P-4 with long polar and charged residues (from Ile and Pro of 40 to Arg and Gln of 41 , respectively). 176 …”
Section: Targeting Cftr-associated Pdz Domain Proteinmentioning
confidence: 99%
“…Furthermore, 41 restored F508del-CFTR-mediated chloride efflux in CFBE cells in Ussing Chamber experiments, similarly to the previously available inhibitor F *- 40 or to the corrector 5 . Structure and energy landscape analysis of the crystal structure of 41 :CALP (PDB ID: 6OV7) showed that the tighter binding efficiency of 41 could stem from entropic effect at P0 and favorable substitutions at P-1 and P-4 with long polar and charged residues (from Ile and Pro of 40 to Arg and Gln of 41 , respectively) …”
Section: Targeting Cftr-associated Pdz Domain Proteinmentioning
confidence: 99%